Asas Nebis In Idem Dalam Perkara Kepailitan - Ritri Riawati; Muskibah Muskibah; Evalina Alissa (Zaaken: Journal of Civil and Business Law, 2021)
The purpose of this research is to find and analyze nebis in idem principle. In bankruptcy proceedings The problem is how the formulation in idem principle nebis in idem in bankruptcy proceedings The methodology used normative.  Juridical namely researchThe results of the research is that both bankruptcy and suspension of debt payment obligation will be nebis in idem principle because no one chapter of UUK PKPU and said that in bankruptcy proceedings and does not apply in principle PKPU nebis in idem but in practice the principle of drop the bankrupt PKPU and this is because this is a rather than a suit and nature of the request in the matter of pkpu. is dynamic and bankruptcy proceedings. Abstrak Tujuan penelitian ini adalah Untuk mengetahui dan menganalisis asas nebis in idem dalam perkara kepailitan. Rumusan masalahnya adalah bagaimana  penerapan asas nebis in idem dalam perkara kepailitan. Metode penelitian yang digunakan yaitu penelitian yuridis normatif. Hasil dari penelitian adalah bahwa di perkara kepailitan dan penundaan kewajiban pembayaraan utang tetap berlaku asas nebis in idem dikarenakan tidak ada satu pasal dari UUK dan PKPU yang menyatakan bahwa di perkara Kepailitan dan PKPU tidak berlaku asas nebis in idem, tetapi  dalam prakteknya hakim menggugurkan asas ini dikarenakan permohonan pailit dan PKPU bentuknya adalah “permohonan” bukannya “gugatan” dan sifat dari alasan permohonan dalam perkara PKPU dan perkara kepailitan adalah dinamis.